2020
DOI: 10.1002/ddr.21743
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of cilostazol among antiplatelet FDA‐approved drugs against COVID 19 Mpro and spike protein: Drug repurposing approach

Abstract: Coronavirus disease 2019 (COVID 19) was first identified in Wuhan, China near the end of 2019. To date, COVID‐19 had spread to almost 235 countries and territories due to its highly infectious nature. Moreover, there is no vaccine or Food and Drug Administration (FDA)‐approved drug. More time is needed to establish one of them. Consequently, the drug repurposing approach seems to be the most attractive and quick solution to accommodate this crisis. In this regard, we performed molecular docking‐based virtual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
(26 reference statements)
0
21
0
2
Order By: Relevance
“…PubChem's database uses the 3D chemical structures of Doxorubicin, Chloroquine, and Tioconazole. Auto Dock 4 was used for docking accounts; then the Molecular Docking Server (https://www.dockingserver.com accessed on 7 July 2019) was used [14], Protein structures and the selected drugs were prepared as previously described [77].…”
Section: In-silico Docking Studymentioning
confidence: 99%
“…PubChem's database uses the 3D chemical structures of Doxorubicin, Chloroquine, and Tioconazole. Auto Dock 4 was used for docking accounts; then the Molecular Docking Server (https://www.dockingserver.com accessed on 7 July 2019) was used [14], Protein structures and the selected drugs were prepared as previously described [77].…”
Section: In-silico Docking Studymentioning
confidence: 99%
“…The authors' recently published docking study suggests the possibility of antiplatelet drugs against COVID-19 [ 24 ]. To prove these drugs' effectiveness, we include molecular dynamics simulation for the SARS-CoV-2 protein targets M pro and the spike protein for 100 ns (see the supplementary figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…The structure of the ligands (FDA- approved Antiplatelets) are retrieved from the PubChem database and prepared for the docking study [ 24 , 25 ]. Additionally, the SARS-CoV-2 M pro and spike protein structures are retrieved from the Protein Data Bank (PDB ID: 6Y84 and 6YLA, respectively).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In silico screening suggests that an antagonist of PGE 2 receptor 4 (EPR4), grapiprant, interferes with the interaction between SARS-CoV-2 and cell surface binding of an immunoglobin protein by locking the substrate binding domain in a closed conformation ( Zhang et al, 2021 ). In addition, a docking-based virtual screening of antiplatelet FDA-approved drugs revealed that iloprost and epoprostenol, two stable prostacyclin analogs, have promising binding interactions with S-protein ( Abosheasha and El-Gowily, 2021 ). However, the impact of these interactions on viral entry or replication has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%